Trends in Search Patterns and Public Interest in Vaping, Cigarette Products, and Oral & Oropharyngeal Cancer: An Infodemiology Analysis - Dipanshu Aggarwal; Poonam Waghmode (Oral Sphere Journal of Dental and Health Sciences, 2026)
Background: It is anticipated that oral & oropharyngeal cancer will continue to rise in the coming decades. Consequently, it is crucial to implement prevention strategies and gain insight into the current state of public awareness and knowledge regarding this ailment. In this context, the field of infodemiology holds a huge significance, as it enables the tracking of trends in health information-seeking behaviours and epidemiology. This study aims to examine and trace the utilisation and progression of internet-based information-seeking behaviours pertaining to head & neck cancer in India, the USA, and across the globe, utilising Google Trends as a primary data source. Methods: Using Google Trends (GT), the following keywords/terms were searched related to smoking as “cigarette” “, smoking” “, tobacco” “, hookah” and “vape” and oral cancer as “oral cancer” “, mouth cancer” “, throat cancer” “, tongue cancer” and “head and neck cancer”. The search volume and trend were analysed from January 2017 to December 2022. Results: The Relative Search Volume Index (RSVI) for "vape" was found to be the highest globally, including in the United States. Surprisingly, in India, searches related to cigarette products were more prevalent, while vaping-related searches were the least common among the compared habits. Conclusion: It is important to know how people look for healthcare information so that we can make sure the information given by health organisations, advocacy groups, and health professionals about head and neck cancers is top-notch and well-planned.